Alkali metal ion codoped Eu3+ activated yttrium orthovanadate with tunable photoluminescence properties for LEDs and anti-counterfeiting applications - Anuradha; Dwivedi A.; Upadhyay S.; Srivastava A.; Srivastava M.; Kumar R.; Srivastava S.K. (My University, 2025)
The present experimental report articulates a comprehensive investigation on the synthesis, structural, and photoluminescence characteristics of M0.05,Eu0.05:Y0.90VO4 (M = Li+, Na+, K+) nanophosphors synthesised by auto-combustion approach, for optical display and anticounterfeiting technologies. Various characterization tools such as X-ray diffractometer (XRD), Transmission Electron Microscope (TEM), Scanning Electron Microscope (SEM), Fourier transform infra-red (FTIR) Spectroscope, and Raman spectroscope have been employed to understand the morphology and crystal structure of M0.05,Eu0.05:Y0.90VO4 (M = Li+, Na+, K+) nanophosphor, which reveals the formation of a pure tetragonal structure and well crystalline phase. Moreover, the UV–Vis spectra, suggests that the as-synthesised material substantiated to possess an energy band gap of ∼3.6 eV conjecturing it as a wide-band material, and the refractive index (n) of the prepared samples has been deduced as ∼ 2.1. Among all alkali ions, Li+-codoped sample exhibits the most intense PL spectra. The enhancement in PL intensity has been observed due to the energy transfer of VO43−→Eu3+ and the codoping of lithium ions acts as a good charge compensator. For the optimized sample CIE coordinates has been found as (0.59, 0.39) and CCT value as 1712 K, which suggest it as a prospective candidate for the warm LEDs. The optimized sample has further been investigated for the visualization of Latent fingerprint on glass slide and as security ink. It displays efficient applicability as a well-defined ridge features up to level III. Henceforth, the as-synthesised Li0.05,Eu0.05:Y0.90VO4 nanophosphor may potentially be applied for multipurpose applications. © 2024 Elsevier Ltd and Techna Group S.r.l.